2022
DOI: 10.1002/adhm.202201661
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Regulation of the Bone Immune Microenvironment via Dam‐Like Biphasic Bionic Periosteum for Bone Regeneration

Abstract: The bone immune microenvironment (BIM) regulates bone regeneration and affects the prognosis of fractures. However, there is currently no effective strategy that can precisely modulate macrophage polarization to improve BIM for bone regeneration. Herein, a hybridized biphasic bionic periosteum, inspired by the BIM and functional structure of the natural periosteum, is presented. The gel phase is composed of genipin-crosslinked carboxymethyl chitosan and collagen self-assembled hybrid hydrogels, which act as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…59 Research has shown that implants with excellent immune-inflammatory regulation ability, which creates an advantageous bone immune microenvironment in the early stage of osteogenesis, can enhance osteoanagenesis. 60,61 As the LBL layers gradually degrade, the remaining RA continues to release, and the cumulative release concentration is about 0.06 mg mL À1 during the subsequent release period, which will promote osteoblast differentiation. 6 The entire release process lasts for at least 21 days, and the long-term release of RA can effectively promote osteoanagenesis in the long osteogenic cycle.…”
Section: Fabrication and Characterization Of Surface-modified Cfrpeekmentioning
confidence: 99%
“…59 Research has shown that implants with excellent immune-inflammatory regulation ability, which creates an advantageous bone immune microenvironment in the early stage of osteogenesis, can enhance osteoanagenesis. 60,61 As the LBL layers gradually degrade, the remaining RA continues to release, and the cumulative release concentration is about 0.06 mg mL À1 during the subsequent release period, which will promote osteoblast differentiation. 6 The entire release process lasts for at least 21 days, and the long-term release of RA can effectively promote osteoanagenesis in the long osteogenic cycle.…”
Section: Fabrication and Characterization Of Surface-modified Cfrpeekmentioning
confidence: 99%
“…According to previous reports, calcium salt deposition and bone matrix mineralization are important stages of bone formation. [29] The formation of calcium nodules in the extracellular matrix was analyzed by Alizarin Red S staining. Coaxial-Si and Bilayer-DFO/ASP/Si produced more calcium nodules on days 7 and 14, significantly higher than Coaxial-B (Figures 5C,D).…”
Section: In Vitro Osteogenesis and Qrt-pcr Analysismentioning
confidence: 99%
“…A rat skull defect model is commonly employed to validate the reparative efficacy of the artificial periosteum. [29,68] It should be emphasized that combining filler repair with an artificial periosteum can significantly enhance its clinical applicability; However, our study is aimed to investigate the effectiveness of biomimetic periosteum in repairing bone defects without incorporating fillers into the rat skull defect model, thus ensuring unambiguous evaluation of the reparative effect. Therefore, to further validate the osteogenic effect of the biomimetic periosteum in vivo, a rat skull bone defect model was established, and replaced the native periosteum with the biomimetic periosteum (Figures 7A and S10).…”
Section: Programmed In Vivo To Promote Regeneration Of Bone-periosteu...mentioning
confidence: 99%
See 1 more Smart Citation
“…Drug-mixing electrospinning method [246] Wound healing Electrospinning method Vitamin K3 carnosine peptide (agent for antibacterial activity)…”
Section: Additional Therapeutic Applications Of the Fibrous Scaffoldsmentioning
confidence: 99%